Exposure to loneliness cues reduces prosocial behavior: Evidence from N400 and P300 - Yin, Meiling; Lee, Eun-Ju (Frontiers in Psychology, 2023)
Loneliness is a major risk factor for morbidity and mortality. However, the effect of loneliness on subsequent prosocial behavior is not well known. Understanding the neurobiological mechanisms underlying loneliness is necessary to address this research gap. We investigate the mechanism using a modified public goods game (PGG) wherein participants can choose to act for a collective or selfish interest after being exposed to loneliness cues. Both behavioral (study 1) and event-related potential (ERP) (study 2) measures were used to explore this relationship. In study 1 (N=131), we found that participants exhibited decreased prosocial actions under the loneliness priming condition as opposed to the control condition. In study 2 (N=17), frontal N400 and posterior P300 components were identified under the loneliness priming condition as opposed to the control condition. Increased (decreased) frontal N400 and posterior P300 lead to selfish (prosocial) choices. These results indicate that humans instinctively perceive loneliness as inconsistency with their desired social-relational life, which in turn stimulates coping strategies for self-preservation. This study contributes to our understanding of the neurobiological basis of loneliness associated with prosocial behavior.